Designing a Longitudinal, Quantitative Measurement of Teachers’ Beliefs about Multilingualism: A Research Protocol - Tobias Schroedler; Anna Ritter; Caroline Böning (Journal of Research in Social Sciences and Language)
An increasing necessity to prepare future teachers to cater for the needs of multilingual learners has led to growing research in education and educational linguistics across the world. This paper presents the methodological design of a longitudinal research project that measures the affective-motivational competence development of pre-service teachers with regard to multilingual learners. The project is based within a large German teacher education programme during which pre-service teachers attend several compulsory modules on multilingualism as part of their early professionalisation. The affective-motivational competence development of two full cohorts of prospective middle school teachers (n = 499) is observed in four test intervals across their five-year programme. The present paper limits itself to reporting on the complex design, the measurement instruments, and the methodological challenges of a longitudinal observation of relevant competence facets. The paper closes with a critical reflection of both the opportunities and the limitations of the research design presented here.